Study and optimization of a renewable system of small power generation - Mohammed Salim Hadjidj; Bibi Triki Faouzi; Didi Faouzi (International Journal of Advances in Applied Sciences, 2018)
In this paper, a study was conducted on the sustainable development of solar and wind energy sources. The approach adopted is to exploit the two renewable resources by arriving to determine optimal configurations of photovoltaic and / or wind energy system with storage to provide electricity to a self-contained residential apartment located in the city of Tlemcen , in Algeria. The Tlemcen site showed a more favourable trend to use the photovoltaic system alone on the hybrid PV / wind system because of the low wind speeds of this site. The calculation method used is based on the monthly averages for ten consecutive years, data collected by the Tlemcen Zenâta weather station in order to have a better reliability analysis of an electric power generation system. In addition, the methods used in this study can be used to determine the optimal size of the most economical hybrid system that corresponds to any site in the world and for any requested load.